İBN RÜŞD’ÜN TE’VİL ANLAYIŞI VE AKTÜEL DEĞERİ ÜZERİNE - Mesut Okumuş (İslami İlimler Dergisi)
Ibn Rushd (Averroes) was an influential, eminent and ratioanlist Islamic thinker of the history of Islamic thought. He educated in theology, Islamic law in his early life and besides them medicine, mathematics and philosophy. He attempted to harmonize religion with philosophy without synthesizing them or obliterating their differences. He believed that the Qur’an contained the highest truth while maintaining that its words should not be taken literally. He argued that religion and philosophy are brothers and does not contradict each other. Ibn Rushd accepts that there are three types of human. The first and largest in number, is receptive to ideas that can be expressed logically; the second is amenable to persuasion and the third, few in numbers, will only be convinced by conclusive evidence. He believed that Qur’an not only contains verses to the simple masses, but also to the enlightened few philosophers highest truths. He gave allegorical interpretation method (tawil) right to the philosophers and adviced them to use al-Ghazali’s five being classification. However, this constrictive attitude and his advices has not been accepted by muslim scholars in general and thelogians, exegetes and lawyers in particular. Moreover, today the meaning and content of the ‘philosopher’ has changed a little bit more and has narrowed.